FrameEST: um framework de componentes, no padrão MVC, para o domínio de biologia molecular - Lombardo, Luiz Roberto (Universidade Federal de São Carlos, 2006)
Nowadays, some projects of genomes of different organisms are being analyzed generating a great volume of data, which are stored in heterogeneous and distributed data sources. Moreover, there are available tools in the genome domain that also need to be integrated. Another problem is that the systems developed for these objectives do not offer all the support to the researchers, therefore in their majority do not possess flexibility and are of difficult expansion. The proposal of this work is the development of a software component framework, called FrameEST, developed with the most recent technologies of reuses, that structures and guides the development of different applications of molecular biology domain. The FrameEST is available for reuses of the applications: in the phase of modeling in a CASE tool and the phase of implementation as one plug-in in the Eclipse enviroment. A case study is used to illustrate the FrameEST reuse.
Keywords: Arquitetura de computador; Framework (Programa de computador); Componentes de software; MVC - Model view control; Biologia molecular; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO